Sistematización y análisis retrospectivo de la casuística equina presentada en los años 2008 y 2009 en la clínica veterinaria San Luís del Departamento de Antioquia, Colombia (2013)
The aim of this study was to perform a retrospective analysis in the "Clinica Veterinaria San Luis" located in the city of "La Estrella", Antioquia, Colombia, for the period from January 1 2008 to December 31 2009, in the equine medicine cases, getting information from the medical records, filled for the equine patients coming for veterinary service consultation in the period, creating a MySQL database for further analysis. A web platform was created with an interface developed in HTML and php, which allowed the entry of information from anywhere in the world having an internet connection. There were evaluated the following variables: species, breed, sex, status, reason for consultation, required examinations, diagnosis, grade, age, weight, among others variables. Some difficulties were found in the interpretation of medical records due to the diversity of people (veterinarians, technicians and veterinary students) involved in the equine clinical care. In the study period 236 patients were registered, Among the characteristics associated to the veterinary service it was presented the Colombian creole horse (86.96%) Colombian and the females with a percentage of 53.9%. The highest percentage of cases corresponded to colic by large colon displacement (10.17%), followed by gastric colic of food fermentation (5.51%), obstructive colic by small colon impaction (enteroliths) (5.08%), and large colon impaction (4.66%) and unilateral cryptorchidism (4.66%). The most common affected system was the gastrointestinal system.